Innovative activity of enterprises of food industry in Ukraine: state and trends of development - Kruhlova, Olena; Pohozhykh, Mykola; Niemirich, Oleksandra; Ustymenko, Ihor; Havrysh, Andrey; Hubenia, Vyacheslav; Matiushenko, Raisa (My University, 2020)
The studies confirmed the hypothesis of the relationship between the innovative activity of food industry enterprises and the level of the knowledge intensity of GDP. There is a high direct relationship between the level of the knowledge intensity of GDP and the number of innovatively active enterprises of the food industry (0.893); high feedback, however, between knowledge intensity and the cost of innovation per one innovation-active enterprise (–0.836); noticeable feedback – between knowledge intensity and the cost of innovation of the food industry (–0.414). The results of the calculations indicate the relevance of further research in this area, namely the study of the impact of knowledge and innovation on the sustainable development of the food industry. Проведені дослідження підтвердили гіпотезу про залежність між інноваційною активність підприємств харчової промисловості та рівнем наукоємності ВВП. Високий прямий зв’язок відзначено між рівнем наукоємності ВВП і кількістю інноваційно активних підприємств харчової промисловості (0,893).; високий проте зворотний зв’язок – між наукоємністю та витрати на інновації на одне інноваційно активне підприємство (-0,836); помітний зворотний зв’язок – між наукоємністю та витратами на інновації підприємств харчової промисловості (-0,414). Результати розрахунків свідчать про актуальність подальших досліджень у цьому напряму, а саме дослідження впливу наукоємності та інновацій на сталий розвиток підприємств харчової промисловості.
Keywords: кафедра технології ресторанної і аюрведичної продукції; кафедра готельно-ресторанної справи; creative activity of the employee; scientific research; gross domestic product; інноваційна діяльність підприємства; наукові дослідження; валовий внутрішній продукт